AirAsia Group Berhad strengthens SuperApp during the Covid-19 Pandemic - Rolina Rahardjoputri; Ronaldo Yolanda Putra; Heru Agustanto (Universitas Sebelas Maret, 2021)
Many times, the world has gone through economic crises and one of the worst is the Covid-19 pandemic. This pandemic has spread across the globe and various policies to limit people's mobility are implemented such as flight restrictions that affect airlines' business. With a significant reduction in the number of passengers, the revenue stream from airline passengers has also decreased significantly. This case study explains the business decisions made by AirAsia in the face of the Covid-19 pandemic. The Covid-19 challenges companies to respond and run their operations in new, effective, and efficient ways to continue the business. We use a descriptive case study approach with PEST (Political, Economic, Social, and Technology) and SWOT analysis (Strength, Weaknesses, Opportunity, and Threats) to determine the internal and external factors used to monitor and evaluate business decisions. We find that AirAsia Group Berhad has an excellent opportunity to make AirAsia’s SuperApp even more developed amidst the Covid-19 pandemic and become a new revenue stream. However, AirAsia management must be wary of its big competitors who are more experienced in digital applications.